PENDRED'S SYNDROME; A CASE REPORT AND REVIEW OF LITERATURES - Jawad kadhim S AL-Dhahiry; Tarik Khalid AL Niamey; Ameer Kadhum Daher; Ramzi Kadhum AL; Biati (The Medical Journal of Basrah University, 2011)
ABSTRACT Thyroid dyshormonogenesis is a rare condition, due to genetic defects in the synthesis of thyroid hormones where patients develop hypothyroidism with goiter. One particular familial form , associated with sensorineural deafness is called Pendred's Syndrome (PS). We report probably a unique case of a young man with PS who developed a large, bulky goiter without a family history of goiter or deafness. The clinical findings were used to illustrate the normal physiology of thyroid hormone synthesis, the mechanisms of iodide transport in the thyrocyte, the pathophysiology of dyhormonogenesis and genetics of Pendred's syndrome.